1996
DOI: 10.1063/1.471440
|View full text |Cite
|
Sign up to set email alerts
|

Heat capacity anomaly near the lower critical consolute point of triethylamine–water

Abstract: The heat capacity of the binary liquid mixture triethylamine-water has been measured near its lower critical consolute point using a scanning, adiabatic calorimeter. Two data runs are analyzed to provide heat capacity and enthalpy data that are fitted by equations with background terms and a critical term that includes correction to scaling. The critical exponent a was determined to be critical exponents. These values, for the most part, agree very well with experimental results. _-3 Several universal amplitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 31 publications
2
32
0
Order By: Relevance
“…The value of R B calculated from equations (27) and (28) was À0.58 ± 0.02. The value of R B calculated by equation (26) from our experimental results was À0.513 ± 0.003, which is in good agreement with the experimental values reported by Jacobs [42,43] and our previous work [15], but smaller than both the prediction of Bagnuls and Bervillier and that of equation (27).…”
Section: Tablesupporting
confidence: 91%
“…The value of R B calculated from equations (27) and (28) was À0.58 ± 0.02. The value of R B calculated by equation (26) from our experimental results was À0.513 ± 0.003, which is in good agreement with the experimental values reported by Jacobs [42,43] and our previous work [15], but smaller than both the prediction of Bagnuls and Bervillier and that of equation (27).…”
Section: Tablesupporting
confidence: 91%
“…It was found that the variation of 0.01 in a caused the changes of about 16%, 11%, 5%, and 1.6% in A + , A À , A + /A À , and C p0 , respectively, while the contribution of the variations of T c and E within their uncertainties to the changes of the adjusting parameters were negligible. It was reported that the theoretical predictions gave the values of A + /A À being (0.537 ± 0.019) for d = 3 expansion [1], (0.530 ± 0.003) for high-temperature series [2], (0.527 ± 0.037) for e expansion [1], and (0.55 ± 0.01) for Monte Carlo simulation [33], while the experimental values were ranged between 0.52 and 0.59 [26,28,30,32,[34][35][36][37][38][39]. The value of A + /A À determined in this study in the temperature range of ±2.8 K from the critical point is 0.533, which is in excellent agreement with the theoretical prediction of 0.530 for hightemperature series.…”
Section: Isobaric Heat Capacity Per Unit Volumementioning
confidence: 92%
“…The value of X was predicted to be (0.01966 ± 0.00017) from an expansion of d = 3 [41], and (0.01880 ± 0.00008) from high-temperature series [2], respectively. Recent experimental determinations have found X to be in the range between 0.019 and 0.028 [28,30,34,36,39,[42][43][44]. Our measurements in the range (T À T c ) = (0 to 2.8) K gave the values of amplitude n 0 of the correlation length and amplitude A + of the heat capacity to be (0.287±0.005) nm and (0.01365 ± 0.00009) J Á K À1 Á cm À3 , respectively.…”
Section: Isobaric Heat Capacity Per Unit Volumementioning
confidence: 99%
“…The heat capacity of a critical mixture was measured using an adiabatic calorimeter similar to that used previously for studies in triethylamine-water 24 and anilinecyclohexane. 20 Our calorimeter was used in a ''step'' mode, where a fixed energy was added to the cell and the resulting temperature step was measured.…”
Section: B Heat Capacitymentioning
confidence: 99%